2015
DOI: 10.1007/s10815-015-0625-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphokinetics of embryos developed from oocytes matured in vitro

Abstract: These findings do not support the hypothesis that maturation in vitro affects embryo morphokinetics, while they suggest only marginal differences in the morphokinetics of embryos developed from oocytes matured in vivo and in vitro in IVM cycles and embryos developed from mature oocytes recovered in stimulated cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Full imaging of the developmental competence of the embryos derived from IVM oocytes is an important task to ascertain feasible ways to improve the IVM technique as a clinical approach. It is clear that the final proof of oocyte developmental competence is its ability to develop a viable pregnancy (Dal Canto et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full imaging of the developmental competence of the embryos derived from IVM oocytes is an important task to ascertain feasible ways to improve the IVM technique as a clinical approach. It is clear that the final proof of oocyte developmental competence is its ability to develop a viable pregnancy (Dal Canto et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Azita Faramarzi et al differences in morphokinetics time points between embryos derived from in vitro or in vivo matured oocytes (Walls et al, 2015;Dal Canto et al, 2016). Also, Roesner and colleagues showed that there were no differences in the tPB2, tPNf, t2, t3, t4 and t5 time points.…”
mentioning
confidence: 99%
“…The results of current research showed that human oocytes matured in vivo or in vitro display no significant differences in terms of their spindle morphology, organelle distribution, cortical particle distribution, and mitochondrial morphology [38,39]. By observing embryos dynamically using time-lapse videos, it was confirmed that oocytes matured in vivo or in vitro showed no significant differences in terms of the morphological dynamics observed during the early development of embryos derived from these oocytes [40]. Another study has also shown that the oocytes matured in vitro and in vivo are different in terms of their organelle function, distribution, and gene expression [41].…”
Section: Clinical Application and Safety Of Ivmmentioning
confidence: 54%
“…The authors concluded that the ultrastructure of matured oocytes from IVM cycles had similar cytoarchitecture in both vitrified-warmed and previtrified oocytes in EM studies ( 111 ) . Dal Canto et al ( 112 ) studied the morphokinetics of embryos derived from in vitro matured oocytes from hCG-primed IVM cycles. Oocytes derived from 8-12 mm follicles were categorized according to the cumulus expansion and expanded cumulus oocytes were evaluated as MII and incubated for 6 hours, whereas others were accepted as GV oocytes and incubated for 30 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes derived from 8-12 mm follicles were categorized according to the cumulus expansion and expanded cumulus oocytes were evaluated as MII and incubated for 6 hours, whereas others were accepted as GV oocytes and incubated for 30 hours. The authors concluded that morphokinetic behavior of both mature and GV oocytes from IVM cycles were comparable and it was suggested that only minimal differences were present in GV and MII oocytes from IVM cycles ( 112 ) . Embryos derived from GV oocyte maturation in stimulated IVF cycles had a high arrest rates and multinucleation rates but meiotic resumption happened normally.…”
Section: Discussionmentioning
confidence: 99%